Remote control of the runway surface - Кривенко, Ю. М. (Proceedings of National Aviation University (archive), 2002)
The system of sensors is considered which allows to control and predict the significance of the main factors influencing the dangerous change of the coefficient, the presence and heightwater layer, condition, air temperature and runway surface coverage